Thickness and stacking geometry effects on high frequency overtone and combination Raman modes of graphene. (5th September 2012) - Li, Dongfei; Zhan, Da; Yan, Jiaxu; Sun, Chenglin; Li, Zuowei; Ni, Zhenhua; Liu, Lei; Shen, Zexiang
<x xml:space="preserve">Abstract</x> We investigate two high frequency Raman overtone and combination modes of graphene named 2D' and 2D + G bands, and located at 3240 and 4260 cm–1, respectively. The graphene thickness and stacking geometry effects for these two modes are systematically studied. The features of the 2D' band, which arises from intravalley double resonance, are not sensitive to the variation of thickness with single Lorentzian peak and fixed linewidth. We explain it theoretically by calculating the phonon dispersion mode in k‐space and find that the flat band region of longitudinal optical phonon near Γ point is the mechanism leading to the 2D' band nonsplit. With the thickness increasing, the band position exhibits blueshift and the linewidth increases for the 2D + G band. With changing thickness and stacking geometry of graphene, the intensities of these two high‐frequency bands show obvious different evolution compared with that of G band. Copyright © 2012 John Wiley & Sons, Ltd.